ON SOME ASPECTS OF THE ORGANIZATION OF EDUCATIONAL WORKS OF TECHNICAL STUDENTS UNIVERSITIES (Pedagogy of Higher and Secondary Education, 2022)
In the article some ways of further perfection of technical universities' students' educational work taking into consideration new conditions of education are discussed.